MAKNA DAN NILAI TRADISI MAKATN SIAM PADA MASYARAKAT DAYAK KANAYATN DUSUN SABORO KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Irfani, Andi (Universitas Lancang Kuning, 2024)
Tradition is a result of customs practiced by a group of people within their customs and beliefs. Traditions are passed down from generation to generation, becoming habits that are considered and viewed as something of high value and meaning by society. This research aims to obtain information about the meaning of the Makatn Siam tradition among the Dayak Kanayatn community in Saboro Village, Sengah Temila District, Landak Regency. In this study, researchers used a descriptive qualitative method with an ethnographic approach to describe and explain a problem based on facts collected as they were at the time the research was conducted. Data collection techniques were carried out through direct observation, interviews, and documentation. The meaning and value of the Makatn Siam tradition in the Dayak Kanayatn community serve as a life guide for every community member who practices it. Meanwhile, marriage is considered sacred and very important for human life to continue their lineage. The stages of implementing the traditional marriage ceremony in the Makatn Siam tradition begin with barawas (proposal process), bakomo' (family consultation), engagement, preparation, pre-wedding (pajajank), preparation during the wedding (batutuk), traditional wedding ceremony, and these stages are still used and preserved to this day.